2016
DOI: 10.1108/jes-05-2013-0063
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Okun’s Law in European Union countries

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
7
12
0
3
Order By: Relevance
“…Maria et al (2008) confirmed that the rate of unemployment and per capita income fluctuate over successive periods, and this is repeated over time, i.e., the dynamic analysis between the positive growth of income and unemployment rates. Economou and Psarianos (2016) also confirmed that Okun's law is robust to alternative specifications. The effect of output changes on unemployment rates is weaker for countries with increased labor market protection expenditures, and it is more persistent for countries with low labor market protection.…”
Section: Literature Reviewsupporting
confidence: 59%
“…Maria et al (2008) confirmed that the rate of unemployment and per capita income fluctuate over successive periods, and this is repeated over time, i.e., the dynamic analysis between the positive growth of income and unemployment rates. Economou and Psarianos (2016) also confirmed that Okun's law is robust to alternative specifications. The effect of output changes on unemployment rates is weaker for countries with increased labor market protection expenditures, and it is more persistent for countries with low labor market protection.…”
Section: Literature Reviewsupporting
confidence: 59%
“…It can be observed that the coefficient derived in the present study corresponds well with the values derived in previous studies of this type conducted by Freeman (2001), Sögner and Stiassny (2002), Ball et al (2017), and Economou and Psarianos (2016). The coefficient derived is smaller in the absolute value than the one in Okun's original article (0.30).…”
Section: Discussionsupporting
confidence: 89%
“…Despite the numerous scientific publications in the researched area, most only address data regarding a particular national economy. However, in recent years, certain studies -for example, Lee (2000), Dogru (2013), Perman and Tavera (2005), Anderton et al (2014), Economou and Psarianos (2016), have attempted to overcome this shortcoming by applying a cross-country analysis of the relationship between unemployment and economic growth in the Eurozone, the European Union, the Organisation for Economic Co-operation and Development, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar results have been found in Europe, where Economou and Psarianos (2016) show that the Okun's relationship is robust across specifications but the sensitivity of output to changes in unemployment is weaker for countries with increased labour market protection expenditures. These findings echo those of Cazes et al (2013) who examine crisis-struck countries and present empirical evidence that the responsiveness in the unemployment rate during the global downturn was lower in countries where workers are afforded greater employment protection.…”
supporting
confidence: 82%
“…Similar results have been found in Europe, where Economou and Psarianos () show that the Okun's relationship is robust across specifications but the sensitivity of output to changes in unemployment is weaker for countries with increased labour market protection expenditures. These findings echo those of Cazes et al .…”
Section: Introductionsupporting
confidence: 73%